ANALISIS PENDAPATAN KERIPIK SUKUN PADA INDUSTRI RUMAH TANGGA âCITRA LESTARI PRODUCTIONâ DI KOTA PALU SULAWESI TENGAH - Made Antara, Samsiarti (AGROTEKBIS, 2016)
Sukun is one of the agricultural commodities that is able to fullfil human necessity in daily life and is considered to have promising market opportunities and prospects. Central Sulawesi possesses a sufficient land of Sukun tree spreading. Sukun now can be processed to made chips, it is able to give benefits to industry. This research aims to determine the revenue earned for the domestic industry, "Citra Lestari Production" in Palu, Central Sulawesi. The appointment of respondent was done intentionally (purposive), by considering that Citra Lestari Production is an industry that processes sukun chips in Palu. The respondent of this research was the head of the company, and one of data sources used in this study consisted of primary data and secondary data. Data analysis tool used was income analysis. The results showed that the income of Citra Lestari Production domestic industry is Rp.4,134,059/month, which is obtained from the selling pruduction Rp.18,900,000/month, and the total production cost, Rp.14,765.94.